2019
DOI: 10.1016/j.immuni.2019.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Butyrophilin-like 3 Directly Binds a Human Vγ4+ T Cell Receptor Using a Modality Distinct from Clonally-Restricted Antigen

Abstract: Graphical Abstract Highlights d BTNL3 binds directly and specifically to Vg4 + TCRs via its IgV domain d The superantigen-like binding mode focuses on germlineencoded TCR regions d In contrast, gd TCR binding to a clonally restricted antigen is CDR3-mediated d Mutagenesis indicates parallels with BTN3A1-mediated activation of Vg9Vd2 T cells SUMMARY Butyrophilin (BTN) and butyrophilin-like (BTNL/Btnl) heteromers are major regulators of human and mouse gd T cell subsets, but considerable contention surrounds whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
159
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(171 citation statements)
references
References 55 publications
11
159
1
Order By: Relevance
“…In brief, pAgs are metabolic products that interact with the butyrophilin family member BTN3A1 and activate Vγ9Vδ2 T cells in a BTN2A1-dependent manner [15,16,18,21,[50][51][52]. BTN2A1 has been shown to interact with BTN3A1 and binds Vγ9 + chains via germline-encoded residues in the hypervariable region 4 (HV4) and CDR2, similar to BTNL3 interactions with Vγ4 + chains [18,19,21]. According to Rigau and colleagues, phosphoantigen reactivity depends on the Vγ9JP CDR3 loop and CDR2 residues of Vδ2 chains, that seem to form a second interaction site with another molecule (potentially BTN3A1) on the TCR surface [43,45,53].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In brief, pAgs are metabolic products that interact with the butyrophilin family member BTN3A1 and activate Vγ9Vδ2 T cells in a BTN2A1-dependent manner [15,16,18,21,[50][51][52]. BTN2A1 has been shown to interact with BTN3A1 and binds Vγ9 + chains via germline-encoded residues in the hypervariable region 4 (HV4) and CDR2, similar to BTNL3 interactions with Vγ4 + chains [18,19,21]. According to Rigau and colleagues, phosphoantigen reactivity depends on the Vγ9JP CDR3 loop and CDR2 residues of Vδ2 chains, that seem to form a second interaction site with another molecule (potentially BTN3A1) on the TCR surface [43,45,53].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, EPCR and annexin A2, as well as phosphorylated metabolites of isoprenoid synthesis, were described as serving as self-antigens that indicate cellular stress [5,[11][12][13]. Most importantly, B7 receptor family-like butyrophilin (BTN) and butyrophilin-like (BTNL) molecules have been implied in the development of specific epithelial and circulating γδ T cell subsets [14][15][16][17] and as direct γδ TCRs ligands [18][19][20][21]. Advances in next-generation sequencing (NGS) analysis of human γδ TCR repertoires, together with the recent identification of γδ TCR ligands, shed light on the vast TCR diversity of human γδ T cells, thereby pointing to a complex role in health and disease.…”
mentioning
confidence: 99%
“…S1G). Although it remains to be tested if any of these positively charged amino acids in the framework regions are involved in recognition of the polyanionic ligands, it is interesting to note that germline‐encoded Vγ sequences were recently shown to be involved in recognition of butyrophilin family members by mouse Vγ7 and human Vγ4 TCRs . Results reported here also demonstrate that the amino acid sequences of CDR3 regions impact the strength of spontaneous reactivity.…”
Section: Discussionmentioning
confidence: 62%
“…In a first attempt to integrate lessons learned from Skint1‐DETC and Btnl1/6‐Vγ7 + IELs while also taking into account the fact that γδ TCRs are able to recognize Ags in an adaptive manner (see Silva‐Santos and Strid), 161 it was suggested that the γδ TCR can combine 2 features by exhibiting a dual reactivity using spatially distinct regions for agonist selection and Ag responsiveness 162,163 . This specific mode of recognition was termed “adaptate” reflecting the blend of innate and adaptive features that is unique to the γδTCR 164 and could recently be supported by a study showing direct binding of a human Vγ4 + TCR and BTNL3 163 . Further evidences for this interesting concept should be obtainable by carefully choosing transgenic TCR‐γ in combination with TCR‐δ lines and analyzing the γδ T cell development in the presence or absence of the respective Btnl‐members.…”
Section: The Butyrophilin Family—a Major Regulator Of γδ Biologymentioning
confidence: 95%